PRAGMATIC CYBER ANALYSIS IN THE MIDDLE EAST CONFLICT NEWS TEXT VIEWS THEO VAN LEEUWEN - Faisol, Yufni; Fitriyah, Rifkah; Fakhrurrazy, Rifky; Fauzy, Ridho (Journal of Pragmatics and Discourse Research, 2022)
The cause of this research discussed is the many problems of interest to readers of middle eastern news on several YouTube channels. His research aims to describe the text of the Middle East conflict news study Wacana Theo Van Leeuwen Discourse. Descriptive methods are used as a type of research. The data obtained is a sentence in the main news text of the Middle East conflict on YouTube. The researcher himself performs the instrument. In the data collection technique using the recording technique, one of them is orthographic sorting power.  The results of his research are the first, in writing the comments of the audience, writing words by bringing up parties who have the authority to be involved in the news. Second, not all of Leeuwen's theories are contained in news texts. Third, Leeuwen's approach is described in the news text of the Middle East conflict based on the speech conveyed.